Fatores organizacionais e a inovação tecnológica em produto desenvolvido sob encomenda para o mercado de energia eólica - Donha, Rogério Gonçalves (Universidade Federal de São Carlos, 2018)
Innovation success depends on the organization combining a range of capabilities and identifying the barriers that can result in failures in the introduction of new products or processes. On the other hand, ETO is the most extreme case in organizations who processing activities of an internal order only after a customer's request. Thus, objective´s paper is to identify the organizational factors that facilitate or inhibits the practice of technological innovation in the development cycle of a product developed to order. To meet this objective is used a single case study in a company who developed Yaw drives for the principals’ wind turbine manufacturers in Brazil. The following factors stands out as facilitators: the rigid hierarchical structure combined with some aspects of the projected structure, the level of cooperation between departments, the autonomy given to workers and the high level of sharing of experiences. The main barriers are: the lack of clarity about the organization's strategy, the low frequency and depth of training offered by the company, lack of a mechanism that allows access and registration of information and the sense of accommodation and resistance to change.
Organizational factors and technological innovation in product developed to order for the wind energy market
Keywords: Fatores Organizacionais; Desenvolvimento de produtos; Engenharia sob encomenda; Inovação; Energia eólica; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO